The effect of COVID-19 on operating costs: The perspective of hotel managers in Antalya, Turkey - Kaplan Ugurlu; Bayram Akay; Sevda Demirel (Tourism & Management Studies)
This paper aims to determine whether coronavirus (COVID-19) causes cost increases in accommodation enterprises and, if any, what are these costs. In addition, operating budgets for 2020, occupancy rates, profitability, the decision to stay on and off, and expectations for next year were evaluated from an executive perspective. In the case study conducted using qualitative research method, multiple case-holistic design was utilized, and data was obtained by semi-structured interview technique. The data obtained were analyzed by frequency, content, and word cloud analysis. 4- and 5-star hotels in Antalya, Turkey's coastal tourism paradise, constitute the universe of research and the sample of 10 hotel managers located in Kemer region of Antalya. COVID-19 has emerged the safety and health measures costs, hygiene and cleanliness costs, and technological tools costs in the hotels. Apart from these, legal restrictions have also shortened the tourism season from 8 months to 4 months in hotel businesses. Occupancy rates of businesses remained between 45-60%. There was also a negative deviation of 60% in the budget targets of the enterprises. Hotel managers focused on capturing breakeven point, keeping staff out of work, and maintaining the hotel's image, rather than achieving the expected profit.